2006
DOI: 10.1002/app.24208
|View full text |Cite
|
Sign up to set email alerts
|

Young modulus and degree of crystallization of highly‐elongated polyoxymethylene

Abstract: ABSTRACT:The physical structure of polyoxymethylene (POM) drawn into two steps by a press and a simultaneous biaxial drawing machine was studied and the drawing dependency on the degree of the crystallization, the orientation, and the modulus were analyzed. The stretching ratio by the press reached 6.0 and the tensile modulus of elasticity increased from 2.5 to 4.5 GPa. However, the degree of crystallization decreased slightly. The rupture elongation increased in the lower drawing region and it peaked when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although the melt spinning of POM fiber was reported in literature, these studies mainly covered the relationship of the orientation degree, take‐up speed, and mechanical properties. For instance, several studies have reported that the orientation degree of lamellar stacks of POM is proportional to the take‐up speed . In the present study, the POM fiber is produced by melt spinning with a high take‐up speed.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the melt spinning of POM fiber was reported in literature, these studies mainly covered the relationship of the orientation degree, take‐up speed, and mechanical properties. For instance, several studies have reported that the orientation degree of lamellar stacks of POM is proportional to the take‐up speed . In the present study, the POM fiber is produced by melt spinning with a high take‐up speed.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, several studies have reported that the orientation degree of lamellar stacks of POM is proportional to the take-up speed. [45,46] In the present study, the POM fiber is produced by melt spinning with a high takeup speed. A strong shear flow field and orientation on the monofilament during crystallization are imposed.…”
Section: Introductionmentioning
confidence: 99%
“…By applying the press drawing followed by subsequent simultaneous biaxial drawing, the tensile modulus reached 11 GPa when the draw ratio was 14 times, and the degree of crystallinity increased from 71% to 76-80%. Additionally, the high tensile modulus of elasticity was obtained and the maximum value was 11.5 GPa at 14 times of the drawing ratio [141].…”
Section: Highly Oriented Productsmentioning
confidence: 99%
“…Polyoxymethylene (POM) is one of the major thermoplastic engineering polymers and it is mainly applied in mechanical parts due to excellent performance against wear, high strength, stiffness, and excellent chemical resistance [1][2][3]. POM is also attractive material for use in biomedical applications such as bone tissue replacement especially in hip prosthesis [4], dentistry [5], and cardiology [6].…”
Section: Introductionmentioning
confidence: 99%